Evaluating the role of social media marketing activities on brand equity of an automobile oil brand in South Africa - Zungu, Mpumelelo Zandile (University of the Witwatersrand, Johannesburg, 2022)
Social media marketing (SMM) plays a significant role in providing access to increased brand activity, brand recognition, and generating online traffic for different businesses for both new and old brands. This study conducted 15 qualitative in-depth interviews with key informants involved in the marketing and sales of the Engen Petronas oil brand in South Africa to explore the impact of social media marketing activities (SMMA) on the new Petronas oil lubricants. The results reveal that SMM activities have proven to be an effective strategy for improving the Petronas oil lubricants brand's brand besides being a new brand in the South African market. Furthermore, the study's findings indicate that despite the lack of significant trendy social media strategies, the engaged SMMA provides access to increased brand activity, brand recognition, and generating online traffic for the Petronas oil lubricant
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2022
Keywords: Social media marketing (SMM); Social media marketing activities; Oil Lubricants; Brand equity; UCTD; SDG-8: Decent work and economic growth